#### Answer

The solutions are $3$ and $2$.

#### Work Step by Step

Isolate $0$ on the right side.
This can be done by moving the terms $9(p+2)-20$ from the right to the left side.
Note that when a term is moved to the other side of an equation, its sign changes to its opposite.
Thus, the equation is equivalent to:
$(p+2)^2-9(p+2)+20=0$
Let $u=p+2$.
Rewrite the equation above using $u$ to obtain:
$u^2-9u+20=0$
Factor the trinomial to obtain:
$(u-5)(u-4)=0$
Use the Zero Factor Property by equating each factor to zero, then solve each equation to obtain:
\begin{array}{ccc}
\\&u-5=0 &\text{or} & u-4=0
\\&u=5 &\text{or} & u=4
\end{array}
Since $u=p+2$, then
\begin{array}{ccc}
\\&u=5 &\text{or} & u=4
\\&p+2=5 &\text{or} & p+2=4
\\&p=5-2 &\text{or} & p=4-2
\\&p=3 &\text{or} & p=2
\end{array}
Therefore, the solutions are $3$ and $2$.